2019
DOI: 10.14814/phy2.14238
|View full text |Cite
|
Sign up to set email alerts
|

FOXN3 controls liver glucose metabolism by regulating gluconeogenic substrate selection

Abstract: The FOXN3 gene locus is associated with fasting blood glucose levels in non‐diabetic human population genetic studies. The blood glucose‐modifying variation within this gene regulates the abundance of both FOXN3 protein and transcript in primary human hepatocytes, with the hyperglycemia risk allele causing increases in both FOXN3 protein and transcript. Using transgenic and knock‐out zebrafish models, we showed previously that FOXN3 is a transcriptional repressor that regulates fasting blood glucose by alterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…The FOXN3 gene locus is associated with fasting blood glucose levels. Hepatic FOXN3 increases fasting blood glucose by inhibiting hepatic glucose utilization while also regulating the expression of amino acid transporters and catabolic enzymes ( 41 , 42 ). Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5 , thereby inhibiting the proliferation of HCC cells in vitro and in vivo ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FOXN3 gene locus is associated with fasting blood glucose levels. Hepatic FOXN3 increases fasting blood glucose by inhibiting hepatic glucose utilization while also regulating the expression of amino acid transporters and catabolic enzymes ( 41 , 42 ). Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5 , thereby inhibiting the proliferation of HCC cells in vitro and in vivo ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…(B) Scatter plot of NAFLD as exposure and T2D as outcome. (41,42). Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5, thereby inhibiting the proliferation of HCC cells in vitro and in vivo (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although the CpG sites in FOXN3 and ZNF264 were not significantly associated with children's BMI‐z score, their p ‐values before FDR correction were close to 1 × 10 −6 (ranked top1 and 2, respectively) in our GWDm analysis and significant differences were found in validation analysis, which suggesting a potential association of the methylation of FOXN3 and ZNF264 genes with children's BMI‐z scores. Moreover, the FOXN3 gene 36 of cg23501836, ZNF264 gene 37 of cg27437574,and SKIV2L gene 38 of cg13015485 have been reported to induce obesity or obesity‐related diseases in animal or adult studies. A recent meta‐analysis with children aged from 2 to 18 years did not found an association between genome‐wide DNA methylation in cord blood and BMI in early childhood, but found little evidence in the childhood or adolescent, this may be explained by a difference in study sample size, age range, and covariates 17 …”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box N3 ( FOXN3 ) belongs to the FOX protein family that plays a critical role in biological processes, such as metabolism and differentiation 48 . A recent study with an adult mouse model found that FOXN3 controls liver glucose metabolism by regulating gluconeogenesis substrate selection 36 ; while another study with Japanese participants found that glucose metabolism disorders induce visceral fat accumulation 49 . Therefore, it is possible that by altering glucose metabolism, FOXN3 methylation increases the risk of overweight and obese states.…”
Section: Discussionmentioning
confidence: 99%
“…4A). In liver, gene sets enriched by pFUS included those associated with the MYC pathway (known to activate multiple glucose utilization enzymes 113 ), and fatty acid/bile acid metabolism. In the intestines, gene expression hallmarks of improved nutrient/vitamin transport and metabolism were apparent; these included significant changes to glycolytic and gluconeogenic gene sets, and markers of improved mitochondrial function.…”
Section: Multiomic Profiling Reveals Pfus-induced Metabolic Coordination Across Organ Systemsmentioning
confidence: 99%